Content-Free Awareness: EEG-fcMRI Correlates of Consciousness as Such in an Expert Meditator - Winter, Ulf; LeVan, Pierre; Borghardt, Tilmann L.; Akin, Burak; Wittmann, Marc; Leyens, Yeshe; Schmidt, Stefan (Frontiers in Psychology, 2020)
The minimal neural correlate of the conscious state, regardless of the neural activity correlated with the ever-changing contents of experience, has still not been identified. Different attempts have been made, mainly by comparing the normal waking state to seemingly unconscious states, such as deep sleep or general anesthesia. A more direct approach would be the neuroscientific investigation of conscious states that are experienced as free of any specific phenomenal content. Here we present serendipitous data on content-free awareness during an EEG-fMRI assessment reported by an extraordinarily qualified meditator with over 50,000 hours of practice. We focused on two specific cortical networks related to external and internal awareness, i.e. the dorsal attention network (DAN) and the default mode network (DMN), to explore the neural correlates of this experience. The combination of high-resolution EEG and ultrafast fMRI enabled us to analyze the dynamic aspects of fMRI connectivity informed by EEG power analysis. The neural correlates of content-free awareness were characterized by a sharp decrease in alpha power as well as increases in functional connectivity in the DAN und decreases in the posterior DMN. We interpret these findings as correlates of a top-down-initiated attentional state excluding external sensory stimuli and internal mentation from conscious experience. We conclude that the investigation of states of content-free awareness could provide valuable input for new methodological and conceptual approaches in the search for the minimal neural correlate of consciousness.